Governance of Fragmented Compliance and Voluntary Carbon Markets Under the Paris Agreement - Ahonen, Hanna-Mari (2022)
Over the past two decades, the emergence of multiple carbon market segments has led to fragmentation of governance of international carbon markets. International baseline-and-credit systems for greenhouse gas mitigation have been repeatedly expected to wither away, but show significant resilience. Still, Parties to the Paris Agreement have struggled to finalize rules for market-based cooperation under Article 6, which are still being negotiated. Generally, there is tension between international top-down and bottom-up governance. The former was pioneered through the Clean Development Mechanism under the Kyoto Protocol and is likely to be utilized for the Article 6.4 mechanism, while the latter was used for the first track of Joint Implementation and will be applied for Article 6.2. Voluntary carbon markets governed bottom-up and outside the Kyoto Protocol by private institutions have recently gained importance by offering complementary project types and methodological approaches. The clear intention of some Parties to use market-based cooperation in order to reach their nationally determined contributions to the Paris Agreement have led to an ongoing process of navigating the alignment of these fragmented carbon market instruments with the implementation of nationally determined contributions and Paris Agreement’s governance architecture. We discuss emerging features of international carbon market governance in the public and private domain, including political and technical issues. Fragmented governance is characterized by different degrees of transparency, centralization, and scales. We assess the crunch issues in the Article 6 negotiations through the lens of these governance features and their effectiveness, focusing on governance principles and their operationalization to ensure environmental integrity and avoid double counting.